Synthesis of Phenalenyl‐Fused Pyrylium Cations: Divergent C−H Activation/Annulation Reaction Sequence of Naphthalene Aldehydes with Alkynes. (11th September 2017) - Yin, Jiangliang; Tan, Meiling; Wu, Di; Jiang, Ruyong; Li, Chengming; You, Jingsong
Abstract: Described herein is the synthesis of stable oxonium‐doped polycyclic aromatic hydrocarbons (PAHs) by the rhodium‐catalyzed C−H activation/annulations of naphthalene‐type aldehydes with internal alkynes. This protocol provides four divergent reaction types, including two unexpected annulations with an oxygen transposition process, which lead to diverse types of phenalenyl‐fused pyrylium cations comprising a four‐, five‐, or six‐ring‐fused π‐conjugated core. The annulations exhibit an exquisite regioselectivity and a high tolerance of sensitive functional groups. These PAHs feature intriguing photophysical properties such as full‐color tunable fluorescence emission, high quantum yield, and positively charged core, and can be reduced easily to the phenalenyl radicals.